Use of IUDs for emergency contraception: current perspectives - McKay R; Gilbert L (Dove Medical Press, 2014)
Rebecca McKay,1 Lynne Gilbert2 1Department of Obstetrics and Gynaecology, Peterborough City Hospital, Peterborough, Cambridgeshire, United Kingdom; 2Department of Contraception and Sexual Health, Cambridgeshire Community Services NHS Trust, Cambridge, Cambridgeshire, United Kingdom Abstract: Emergency contraception is an essential intervention for the prevention of unplanned pregnancy worldwide. The copper intrauterine device (IUD) is highly effective at preventing pregnancy after unprotected sex or contraceptive failure. Unfortunately, its usage in this context is low and far exceeded by hormonal forms of emergency contraception. These have higher failure rates and, unlike the IUD, are not effective post-fertilization. This review aims to summarize the literature surrounding IUD use as emergency contraception, contrast it with the hormonal options, and provide suggestions for increased usage. Keywords: levonorgestrel, ulipristal acetate, copper intrauterine device